Valorization of Shara Mountain lakes using diatom flora compositions - Levkov, Zlatko; Krstić, Svetislav; Noveska, Marina (Macedonian Journal of Ecology and Environment, 2001)
During summer months in 1995-1998 period, diatom microflora material from 20 lakes on Shara mountain has been collected. Microflora analysis revealed 202 taxa, 83 of them being rare or endangered species in Macedonian flora and 30 being reported for the first time. Most richest in diatom microflora were Crno, Malo Crno, Gorno Dobresko lakes and the lakes in the vicinity of river Pena source. It is of immense importance these hot spots of biodiversity to be protected of the possible antropogenic pollution of any kind due to protection of determined rare microflora.